Clinical and Bacterial Characteristics of Klebsiella pneumoniae Affecting 30-Day Mortality in Patients With Bloodstream Infection - Wu, Xingbing; Shi, Qingyi; Shen, Shimo; Huang, Chen; Wu, Hongcheng (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Limited studies using clinical characteristics and whole-genome sequencing together to fully identify risk factors of patients with Klebsiella pneumoniae (KP) bloodstream infection (BSI). Methods: The present study elucidated clinical and bacterial factors (including sequence type (ST), serotype, resistance, and virulence genes) associated with 30-day mortality of KP BSI at a tertiary hospital. Results: Of 79 eligible patients, the 30-day mortality rate of KP BSI patients was 30.4%. Multivariate analysis showed that the host-associated factors (increased APACHE II score and septic shock) exhibited strong associations with increased 30-day mortality. For the pathogenic factors, carriage of iutA (OR, 1.46; 95%CI, 1.11-1.81, P=0.002) or Kvar_1549 (OR, 1.31; 95%CI, 1.02-1.69, P=0.043) were independent risk factors, especially when accompanied by multidrug-resistance phenotype. In addition, ST11-K64 hypervirulent carbapenem-resistant KP co-harboured acquired blaKPC-2 together with iutA (76.5%, 13/17) and Kvar_1549 (100%, 17/17) genes. They were clustered together based on phylogenetic tree and associated with relatively high mortality. Conclusion: The treatment of critically ill patients infected with KP harboring iutA, Kvar_1549 or ST11-K64 phenotype should require careful management for improving their outcomes.